(untitled) (REMUNOM, 2024)
Thisstudywasdevelopedbasedon a bibliographical review ondomesticviolenceagainstchildrenandtheimpactsonchildren’s mental health. The researchincludedtheanalysisofselectedarticlesfrom CAPES (Coordination for theImprovementofHigherEducationPersonnel), Scholar GoogleandSciELO (ScientificElectronic Library Online) databases. The reportsummarizesthemaintopicsrelatedtothetopic, exploringhowthisinformationcontributestotheunderstandingofthephenomenonofdomesticviolenceagainstchildrenandtheimplicationsonchildren’s mental health.